2017
DOI: 10.1016/j.ymthe.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Delivery of Tumor-Targeted Bax-Derived Membrane-Active Peptides for the Treatment of Melanoma Tumors in a Humanized SCID Mouse Model

Abstract: Melanoma is a highly metastatic and deadly form of cancer. Invasive melanoma cells overexpress integrin a v b 3 , which is a well-known target for Arg-Gly-Asp-based (RGD) peptides. We developed a sophisticated method to synthetize milligram amounts of a targeted vector that allows the RGD-mediated targeting, internalization, and release of a mitochondria-disruptive peptide derived from the pro-apoptotic Bax protein. We found that 2.5 mM Bax[109-127] was sufficient to destabilize the mitochondria in ten differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 69 publications
(82 reference statements)
1
18
0
Order By: Relevance
“…We selected a well‐known cyclopeptide containing the triad sequence Arg‐Gly‐Asp (cRGD), which is one of the most potent ligand for the α v β 3 integrins that are overexpressed in tumor microenvironment . We previously demonstrated that the multivalent presentation of cRGD onto a cyclopeptide scaffold provides an efficient tumor delivery system and imaging agent especially for fluorescence‐guided surgery . Here, we synthesized fluorescent mono‐ and tetravalent RGD‐based conjugates (Scheme ) to evaluate their binding potency.…”
Section: Resultsmentioning
confidence: 99%
“…We selected a well‐known cyclopeptide containing the triad sequence Arg‐Gly‐Asp (cRGD), which is one of the most potent ligand for the α v β 3 integrins that are overexpressed in tumor microenvironment . We previously demonstrated that the multivalent presentation of cRGD onto a cyclopeptide scaffold provides an efficient tumor delivery system and imaging agent especially for fluorescence‐guided surgery . Here, we synthesized fluorescent mono‐ and tetravalent RGD‐based conjugates (Scheme ) to evaluate their binding potency.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Karageorgis et al 64 . described a new and sophisticated method of inducing cellular apoptosis by using integrins.…”
Section: Integrin‐targeted Therapeuticsmentioning
confidence: 99%
“…Previously, RAFT‐ c (RGDfK) 4 was conjugated to a Bax proapoptotic protein derived peptide across a disulfide bridge (RAFT‐c[RGD] 4 ‐S‐S‐depsi‐cgg‐Poro2D). This conjugate displayed a dose‐dependent toxicity against Me275 and Colo829 human melanoma cell lines and induced tumor growth inhibition in Me275 xenografts . However, the RAFT‐poropeptide conjugate showed a biological activity in the micromolar range, and, therefore, high amounts of the compound were necessary for the treatment.…”
Section: Figurementioning
confidence: 99%
“…In agreement with the data presented above,the multimeric conjugate 6 showed approximately three-fold increased activity Finally,c onjugation of the tetravalentR GD-ligand to the antimitotic agent cryptophycin across intracellularly cleavable linker,h as dramatically improved the potencyo ft argeted SMDC based on this ligand, compared to the previously reported RAFT-c[RGD] 4 -S-S-depsi-cgg-Poro2D conjugate. [23] These results underscore the importance of using highly active cytotoxic agentsi nthe context of targeted therapy and show promise for future applicationo ft his payload and its derivatives.…”
mentioning
confidence: 90%
See 1 more Smart Citation